STREET CHILD MANAGEMENT POLICY AT SOCIAL OFFICE OF MAKASSAR CITY, INDONESIA - Solong, Aras; Rahman, Mariati; Aras, Dzulqarnain; Alim, Andi (International Journal of Research -GRANTHAALAYAH, 2023)
The purpose of this research is to find out the policies implemented by the government and to identify what factors are inhibiting and encouraging the government in carrying out policies to deal with the problem of street children in the city of Makassar. Research method the research conducted in this research is qualitative. This study uses a descriptive qualitative approach. The reason for using qualitative is the experience of researchers where this method can be used to find and understand the meaning of a phenomenon that is sometimes difficult to understand. Descriptive qualitative research seeks to describe, record, analyze, and interpret current conditions. The results of this study are road-based coaching; The purpose of this service is to prevent street children in the category of children working on the street from falling into the trap of becoming criminals. Efforts are made for them to live decent lives. Community-based coaching; Social services for street children are focused on the community environment, based on where they live. This service involves all families and street children, as well as all members of the community. In this service, the aim is to prevent children from poor families who have a high risk of becoming street children. So that they don’t have the opportunity to take to the streets and be sure to be returned to their families. Centre-based coaching; Children caught in raids will be recorded and then rehabilitated. This service aims to heal them from the physical, psychological, and social injuries they have experienced, after recovering from the influence of street children’s lives, then they can return to their families. They are given guidance and facilities during their rehabilitation.